Association between SII and hepatic steatosis and liver fibrosis: A population-based study - Xie, Ruijie; Xiao, Mengde; Li, Lihong; Ma, Nengqian; Liu, Mingjiang; Huang, Xiongjie; Liu, Qianlong; Zhang, Ya (Frontiers in Immunology, 2022)
Abstract Background: The systemic immune-inflammatory index (SII) is a novel marker of inflammation, and hepatic steatosis and fibrosis are associated with inflammation. This study aimed to investigate the possible relationship between SII and hepatic steatosis and fibrosis. Methods: The datasets from the National Health and Nutrition Examination Survey (NHANES) 2017-2020 were used in a cross-sectional investigation, Multivariate linear regression models were used to examine the linear connection between SII and CAP and LSM. Fitted smoothing curves and threshold effect analysis were used to describe the nonlinear relationship. Results: This population-based study included a total of 6792 adults aged 18-80 years. In a multivariate linear regression analysis, a significant positive association between SII and CAP was shown [0.006 (0.001, 0.010)]. This positive association in subgroup analysis was maintained in men[0.011 (0.004, 0.018)], but not in women. Furthermore, the association between SII and CAP was nonlinear, using a two-segment linear regression model, we found an inverted U-shaped relationship between SII and CAP with an infection point of 687.059 (1000 cells/uL). The results of the multiple regression analysis showed that the relationship between SII and LSM was not significant (P=0.263). Conclusions: Our findings imply that increased SII levels are linked to hepatic steatosis, but SII is not linked to liver fibrosis. To confirm our findings, more large-scale prospective investigations are needed.